PENGARUH TAMPILAN DAN KONTEN TERHADAP EFEKTIVITAS PROMOSI MELALUI WEBSITE PADA PT.ELEGANT TOUR AND TRAVEL MEDAN - Ariani, Angela; Banjarnahor, Destri Natali (Sekolah Tinggi Pariwisata AMPTA, 2018)
The research is a quantitative research that aims to determine the effect of the display and content on the effectiveness of promotions through the website on PT. Elegant Tour and Travel Medan.This research is conducted by observing PT. Elegant Tour and Travel Medan's website directly. Data collection methods are conducted by spreading online questioners to 96 respondents. The sample selection technique using random sampling. Data from 96 respondents were then analyzed through multiple linear regression analysis with the help of SPSS 20.The result showed adjusted r square value of 0,440 means that 44% of the effectiveness of promotion through the website is influenced by display and content while about 56% is influenced by another factors out of research. The result of testing regression coefficient simultaneously obtained f count of 38,324 > f table which is 3,09 with significance value 0,000 < 0,05. Partial result of hypothesis testing obtained t count of display > t table content (2,275>1,98552) and t count content > t table (8,077>1,98552). From this test it can be conclude that display and content have a positive and significant effect on the effectiveness of promotion through the website on PT. Elegant Tour and Travel Medan. Keyword : Display, Content, The Effectiveness Of Promotion Through The Websit